Clinical Presentation of Dengue in 150 Admitted Cases in Dhaka Medical College Hospital (Journal of Medicine, 2008)
Dengue fever was not recognized as a major public health hazard in Bangladesh before 1999 outbreak, so there was little evidence and awareness in this regard. A prospective observational study was carried out to determine the risk group of patients suffering from dengue syndrome; clinical parameters of the subjects for hospitalization and the pattern of presentation of dengue fever in hospital care in different medicine units of Dhaka Medical College hospital from July 2000 to March 2001. Total 150 cases were selected randomly and diagnosed clinically as dengue, and were classified into 3 groups, i.e. 18 cases of classical dengue fever, 127 cases of dengue hemorrhagic fever (DHF-I and DHF-II) and 5 cases of dengue shock syndrome (DSS), and were discharged uneventfully. Among them 125(83.3%) were male and 25(16.7%) were female. Mean ages of the subjects were 26.75 ±3.69, 27.59 ± 1.18 and 10.67 ± 2.33 years in respective groups. Mean temperature was 103.45±0.28, 103.08±0.13, and 104.00±1.00 °F with mean duration was 5.50±0.51 days, 6.12±0.2 days, and 5.00±1.15 in respective groups. Majority had profound weakness, headache, myalgia, anorexia, nausea, and vomiting. Diarrhoea, abdominal pain, organomegaly, ascites, and pleural effusion were frequent complaints in group-3 patients, whereas infrequent complaints in other groups. Haemorrhagic manifestations were common in group 2 and 3 patients, melaena being the most common manifestations.   DOI = 10.3329/jom.v7i1.1355 J MEDICINE 2006; 7: 3-9